The Muhammadiyahâ€™s 47th Congress and â€œIslam Berkemajuanâ€ - Ali, Muhamad (Studia Islamika, 2015)
The Muhammadiyahâ€™s 47th congress or muktamar in Makassar, South Sulawesi, 18-22 Syawwal 1436 H or 3-7 August 2015, had its theme â€œEnlightenment Movement toward A Progressive Indonesiaâ€. In the opening ceremony, the chairman of the central board, Din Syamsuddin, took the occasion to propose that three of the Muhammadiyahâ€™s leaders, namely Kahar Mudzakir, Ki Bagus Hadikusumo, and Kasman Singodimejo, be recognized as national heroes. President Ir. Joko Widodo has yet to respond to the proposal, but expressed his high appreciation for the Muhammadiyahâ€™s contributions as the enlightenment and progressive movement to the Muslim community and the nation through its schools and universities, hospitals, and others. Joko Widodo pointed to the challenge of the nationâ€™s plurality, and invited participants to continue to give their enlightening contributions to the nation and to the world.DOI:Â 10.15408/sdi.v22i2.1978